2017
DOI: 10.1002/capr.12142
|View full text |Cite
|
Sign up to set email alerts
|

Significant events in an Internet‐delivered (Space from Depression) intervention for depression

Abstract: Objective The advantages and effectiveness of Internet interventions have been established. Little is known about the critical processes of change in Internet‐delivered interventions and of the psychological experience of users. These are both clinically relevant and have a link to the overall outcome of therapy. The goal of this article was to gain an insight into the important therapeutic processes in an 8‐week supported online self‐administered CBT‐based treatment for depression. Method Respondents were par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…This study replicates a number of themes found in previous studies which involved different participants, different interventions, and different methodologies (Lillevoll et al , 2013; Richards and Timulak, 2013; Wilhelmsen et al , 2013; Johansson et al , 2015; Richards et al , 2016; Earley et al , 2017; Holst et al , 2017; Walsh and Richards, 2017; Burke et al , 2018; Richards et al , 2018a). These previous studies lend weight to the current study's findings.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This study replicates a number of themes found in previous studies which involved different participants, different interventions, and different methodologies (Lillevoll et al , 2013; Richards and Timulak, 2013; Wilhelmsen et al , 2013; Johansson et al , 2015; Richards et al , 2016; Earley et al , 2017; Holst et al , 2017; Walsh and Richards, 2017; Burke et al , 2018; Richards et al , 2018a). These previous studies lend weight to the current study's findings.…”
Section: Discussionsupporting
confidence: 86%
“…This need for greater support has also been found for eCBT, even with telephone contact (Holst et al , 2017), so the finding that participants in this study felt they could form a therapeutic relationship online seems a significant improvement: Knowles et al (2015) theorised that greater support could enhance the experience for patients, and this appears to be the case. The current study fleshes out and supports the findings of previous studies into eCBT by providing more detail about how patients can positively experience the supporter's presence and feedback (Richards and Timulak, 2013; Wilhelmsen et al , 2013; Richards et al , 2016; Earley et al , 2017; Walsh and Richards, 2017; Burke et al , 2018; Richards et al , 2018a).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations